Tribological study on rapeseed oil with nano-additives in close contact sliding situation - Gupta R.N.; Harsha A.P.; Singh S. (My University, 2025)
The present work deals with the tribological evaluation of three types of nano-additives, i.e., copper oxide (CuO; ≈ 151.2 nm), cerium oxide (CeO2; ≈ 80 nm) and polytetrafluoroethylene (PTFE; ≈ 90.4 nm) with rapeseed oil under steel–steel sliding contacts. The nano-additives concentrations in the base oil were 0.1, 0.25 and 0.5% w/v for the lubricant formulation. Further, the rapeseed oil was also epoxidized by a chemical method and the tribological behavior was compared with the base oil (unmodified oil) at similar nano-additives concentrations. The ASTM standards were followed for the study of wear preventive and extreme-pressure analysis of nanolubricants, and it was carried out using four-ball tester. In the antiwear test, CeO2 and PTFE nano-additives have shown the significant reduction in the wear scar diameter at the concentration of 0.1% w/v. In the extreme-pressure test, 0.5% w/v concentration was optimum for oxide nanoparticles; however, PTFE nanoparticles did not show positive effect with both the base oils. Different characterization techniques were employed to confirm the oil modification and for the study of the worn surfaces. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.